Hlapivi spojevi arome kupreške janjetine - Krvavica, Marina; Ganić, Amir; Begić, Munevera; Đugum, Jelena (2020)
Within the project of determining the aroma profiles of various Croatian lamb species, whose main objective was to offer a simple and reliable analytical method that could confirm their authenticity by linking them to a geographical breeding area, an analysis of volatile compounds of the Kupres lamb grown on the Kupres Plateau (BiH), at about 1200 m above sea level, was carried out. The considerable territorial separation (horizontal and vertical) of the Kupres Plateau from the Croatian territories where the study was organised (Lika, Dalmatian hinterland, the islands of Pag and Cres) and the differences in their natural characteristics contribute to the reliability of drawing conclusions about possible lamb biomarkers that could be associated with the floral composition of a geographical breeding area. A total of 66 volatile compounds were isolated by the GC-MS analysis (SPME method) of heat-treated Kupres lamb, of which 14 aldehydes (61.55 % of the total peak area), 10 alcohols (7.78 %), 12 ketones (12.11 %), 8 aliphatic hydrocarbons (1.23 %), 7 aromatic compounds (9.63 %), 3 heterocyclic compounds (0.95 %), 1 furan (1.34 %), 2 acids and 3 esters (3,75 %), 4 terpenes (0.94 %) and 3 sulphur compounds (0.73 %). In relation to Dalmatian, Pag, Lika and Cres lamb, the aroma of Kupres lamb contains 3 volatile compounds (2 ketones and 1 ester) which have not been identified in the mentioned types of lamb. Furthermore, the aroma of Kupres lamb contains notably more C-7 aldehydes (16.24 %), ketones 2,3-octadienone and 2-octanone (9.96 %) and long-chain alkanes (0.71 %), that are reported by other researches as pasture markers, but also a much smaller amount and content of terpenes (0.94 %), that are reported as possible reliable biomarkers of the geographical breeding area. Since terpenes are solely metabolites of plants (dicotyledons contain much more terpenes than monocotyledons), mainly incorporated directly from food into animal tissues, the terpenic profile of
Dentro del proyecto de determinar los perfiles de aroma de diferentes especies de corderos croatas, cuyo objetivo principal fue ofrecer un método analítico simple y fiable que pudiera confirmar su autenticidad al vincularlos a un área de cría geográfica, fue hecho el análisis de los compuestos volátiles de cordero de Kupres criado en la meseta de Kupres (Bosnia y Herzegovina) a unos 1200 m sobre el nivel del mar. El alejamiento territorial considerable (horizontal y vertical) de la meseta de Kupres de los territorios croatas donde fue hecha la investigación (las regiones de Lika, Dalmatinska zagora y en las islas de Pad y Cres) y las diferencias en sus características naturales contribuyen a la fiabilidad de las conclusiones sobre los posibles biomarcadores de la carne de cordero que podrían asociarse con un área geográfica de cría respecto a la composición floral. El análisis de los compuestos volátiles de carne de cordero tratado térmicamente por la microextracción en fase sólida (SPME) y determinados por la cromatografía de gases-espectrometría de masas (GC-MS), fueron aislados 66 compuestos en total, de los cuales fueron 14 aldehídos (61,55 & del área de pico total), 10 alcoholes (7,78 &),12 cetonas (12,11 &), 8 hidrocarburos alifáticos (1,23 &), 7 compuestos aromáticos (9,63 &), 3 compuestos heterocíclicos (0,95 &), 1 furano (1,34 &), 2 ácidos y 3 ésteres(3,75 &), 4 terpenos (0,94 &) y 3 compuestos de azufre (0,73 &). En comparación con el cordero de Dalmacia, Pag, Lika o Cres, el cordero de Kupres contiene 3 compuestos volátiles (2 cetonas y 1 éster) no identificados en otros tipos de corderos mencionados. Además, el aroma del cordero de Kupres contiene considerablemente más aldehídos C-7 (16,24 &), cetonas 2,3-octadienona, 2-octanonas (9,96 &) y alcanos de cadena larga (0,71 &), mencionados en otras publicaciones como marcadores de pasturas, pero también la cantidad cons
Bibliografija: 30 jed.
Sažetak ; Abstract ; Zusammenfassung ; Resumen ; Riassunto.
Keywords: Janjetina -- Kupreška janjetina -- Kupreška pramenka -- Hlapljivi spojevi -- Aroma profil